Reducing Misperceptions About Very Low Nicotine Content Cigarettes: Insights From Adults Who Smoke. Issue 12 (7th July 2022) - Ranney, Leah M; Jarman, Kristen L; Clark, Sonia A; Baler, G; Gourlay, Margaret; Brewer, Noel T; Goldstein, Adam O; Byron, M Justin
Abstract: Introduction: Many people incorrectly think that very low nicotine content (VLNC) cigarettes are less carcinogenic than current cigarettes. This risk misperception by people who smoke could reduce motivation to quit under a nicotine reduction policy. We qualitatively examined perspectives on campaign messages designed to reduce misperceptions. Aims and Methods: Adults who smoke from North Carolina participated in online interviews. After being introduced to the idea of a VLNC policy, participants were shown VLNC messages and asked about their perceptions on the clarity, understandability, persuasiveness, and meaning of the messages. We conducted a thematic content analysis of the transcripts. Results: Thirty adults who smoke cigarettes participated (15 females, 13 males, 2 nonbinary) with a mean age of 43 years. Central themes that emerged were: (1) Confusion about the proposed VLNC cigarette policy affected how messages were interpreted; (2) Messages that promote self-efficacy for quitting rather than guilt or fear were better received; and (3) Direct and succinct messages were seen as more able to grab attention and inform people who smoke. Some participant concerns focused on whether VLNC cigarettes would relieve their nicotine cravings and whether they would need to smoke more VLNC cigarettes to feel satisfied. Conclusion: Campaign messages to educate the public about the harmful effects of smoking VLNC cigarettes may be more effective if people who smoke are informed about the policy's rationale to understand why nicotine is removed rather than the other harmful chemicals. Messages should also acknowledge the difficulty of quitting and be short and direct to capture attention. Implications: Adults who smoke have some confusion about nicotine reduction in cigarettes and this affects how they perceive potential communication campaign messages about the risk of smoking VLNC cigarettes. In our qualitative research, we found that adults who smoke prefer messages about VLNC cigarettes that acknowledge the challenge of quitting and that are direct and succinct. With further development, campaign messages may be able to reduce misperceptions about VLNC cigarettes and maximize the public health benefit of a nicotine reduction policy.